The Resurrection of Jesus and Human Beings in Medieval Christian and Jewish Theology and Polemical Literature - McMichael, Fr., Steven J (Studies in Christian-Jewish Relations, 2011)
The resurrection of Jesus was considered by Paul and the early Christians as the central truth claim of Christian faith (1 Corinthians 15). This article shows how the resurrection of Jesus was argued by medieval Christians in their polemical literature and how medieval Jews approached the same subject matter.